IDENTIFIKASI EKSTRAK BUAH NIPAH (Nypa Fruticans Wurmb) DENGAN VARIASI MASSA MENGGUNAKAN PELARUT METANOL - Debora Ariyani Panjaitan (LPPM Politeknik LP3I Medan, 2020)
Indonesia has many sources of vegetable oil that can be used as a renewable energy source. One of the vegetable oil sources with great potential to be developed is palm fruit (Nypa Fruticans Wurmb). Nipah fruit is one of the raw materials used in this study, using the extraction method and methanol as the solvent. The research was conducted with various mass variations of 30 grams, 35 grams, 40 grams, 45 grams and 50 grams. The extracted oil is characterized by a fragrant odor, clear yellow color and is volatile. From the results of the extraction of nipah fruit then tests were carried out which included% Yield, pH, Free Fatty Acid (FFA), Iodine Number and Density. From the test results, it was found that the average yield of palm fruit oil was 11.634%, where the highest% yield was found in the 35 gram sample, the pH number for 5 samples showed the number 6,% FFA of palm fruit oil on average 0.8%, the iod number of fruit oil nipah an average of 0.0272 and the specific gravity of nipah fruit oil an average of 0.654 gram / ml.